Analyzing travellers’ irrational routing behaviour - Koh, Hwee Ru (2019)
Singapore society is well-known for being incredibly fast-paced and competitive (Chia et al., 2015), at one point even coined by the BBC as the most ambitious country in the world in a 2018 article (Keating, 2018). There is as such, much to find out about how this would translate into the specific behaviour of residents in Singapore in the travel aspect of their lives. By extrapolation, it is expected for the travel behaviour of Singapore travellers to follow the same trend: always seeking the shortest route possible, no matter what. However, the opposite has been observed and hypothesised, which is that some travellers adopt an irrational pre-trip decision-making behaviour and choose not always to seek the shortest travel time paths possible. In characterising the overall behaviour of an individual, a behavioural concept has been proposed by Schwartz et al. (2002): satisficing and maximising. In general, a Satisficer is known to be accepting of the less ideal choice while a Maximiser always aims for the best option available. With this in mind, this study aims to verify and study the irrational behaviour of travellers in Singapore and the link between travellers’ behaviours and the behavioural concept proposed by Schwartz et al. (2002).